Using structural equation model to estimate nitrate pollution in the Melen Watershed of the Turkey - Ernur Akıner, Muhammed (Journal of Engineering & Processing Management, 2019)
In this study, Bayesian technique was applied in order to estimate export coefficients for the Melen Watershed. Furthermore, instead of calculating the contributions of subwatersheds individually, the whole watershed was considered for the estimation of the total load at the outlet of the Melen Watershed using the calculated nitrate export coefficient. The Bayesian approach has the goal of combining prior knowledge with data to optimally use both sources of information. Success of the Bayesian approach is directly proportional to sufficiency of data for acquiring the prior information about estimands. Bayesian analysis was conducted through Structural Equation Model (SEM) using AMOS software and posterior information about land use based export coefficients was obtained through Markov Chain Monte Carlo (MCMC) method. Estimated land use based nitrate export coefficients are in kg/km2/day unit. In addition, monthly river retention value of nitrogen in all subwatersheds of the Melen Watershed were estimated. This information was used in order to predict nitrate export coefficients appropriately. This study is aimed to be an important precedent for other basins that are determined as in priority in terms of pollution by The Ministry of Forest and Water Works of Turkey.